Lord's resistance army: a story of violence in North Central África (1987-2018) - Santamaría Escobar, María José (2021)
The following dissertation paper follows the armed organization Lord's Resistance Army of Uganda to learn if this group can be classified as a terrorist group resulting from a deconstructed identity from a defense group. For this purpose, this research starts from the modern beginnings of Uganda to suggest the relation of this country with the creation of said group. This investigation is based on the Constructivism theory of Onuf, Wendt, Ruggie, and Reus-Smit to set the formation and progress of concepts such as identity, structures, interests, and their role in our actions. This paper was developed with a qualitative historical, descriptive approach with a non-probabilistic sampling, which helped us figure out that this group was indeed created because of this country's past. Throughout the years, the group's character changed to a terrorist organization because of the subsistence of the leaders and the group itself. This dissertation suggests that the LRA are terrorists since the beginning of the 21st century, under Alex Schmid's terrorism, because of the psychological message of terror they sent to the governments and populations since then.